Lipids in membrane dynamics during autophagy in plants. (13th November 2017) - Enrique Gomez, Rodrigo; Joubès, Jérôme; Valentin, Nicolas; Batoko, Henri; Satiat-Jeunemaître, Béatrice; Bernard, Amélie
Abstract : Autophagy relies on the biogenesis of unique and specialized membrane compartments called autophagosomes. This review focuses on the critical requirements and functions of lipids in the formation of such compartments. Abstract: Autophagy is a critical pathway for plant adaptation to stress. Macroautophagy relies on the biogenesis of a specialized membrane named the phagophore that maturates into a double membrane vesicle. Proteins and lipids act synergistically to promote membrane structure and functions, yet research on autophagy has mostly focused on autophagy-related proteins while knowledge of supporting lipids in the formation of autophagic membranes remains scarce. This review expands on studies in plants with examples from other organisms to present and discuss our current understanding of lipids in membrane dynamics associated with the autophagy pathway in plants.